Correlation of Field‐Moist, Oven‐Dry, and Air‐Dry Soil Potassium for Mid‐Atlantic USA Soybean. Issue 6 (19th October 2017) - Williams, Anna S.; Parvej, Md. Rasel; Holshouser, David L.; Frame, William H.; Reiter, Mark S.
Abstract : Core Ideas: Soil K extracted by each processing method were similar and strongly correlated with relative yield. Soil K from FM, AD, and OD soils were equally good in predicting yield response to fertilizer‐K. Soil drying should not be an issue of concern in extracting soil K from soils in the US Mid‐Atlantic. The extractable soil‐K concentration, used for fertilizer‐K recommendations, may be affected by soil drying. Although air or oven drying are the most common soil processing methods, K from field‐moist soil has been documented to be a better predictor of soil‐K availabilities and fertilizer‐K needs for soybean [ Glycine max. (L.) Merr.] grown on fertile silt loam to clayey soils. We evaluated the effect of four soil processing methods (field‐moist [FM], air‐dry [AD], air‐dry followed by oven‐dry [ADOD], and oven‐dry [OD]) in predicting extractable soil‐K availability for soybean production on less fertile Mid‐Atlantic sandy‐textured soils. Twelve soybean field trials were conducted in 2014 on Coastal Plain and Piedmont soils in Virginia and North Carolina. Soil K was extracted by Mehlich‐1 with each soil processing method and correlated with soybean relative yield. Soil‐K concentrations from each method were statistically similar and strongly correlated ( r 2 = 0.94–0.98) with each other having intercept and slope coefficients that were not different from zero and one, respectively. Extractable soil‐K concentrations from each method were also strongly correlated with soybean relative yield and explained 93 to 95% of the relative yield variation for FM soil, 95 to 96% for AD soil, 83 to 86% for ADOD soil, and 94 to 95% for OD soil. Results suggest that soil‐K concentrations from FM, AD, and OD samples are similar in predicting K availability for soybean. Soil drying should not be an issue of concern in extracting soil K and recommending fertilizer‐K rate for soybean production on Mid‐Atlantic coarse‐textured Coastal Plain and Piedmont soils.